Rosyjskie modele zdań za znaczeniem żalu w kon frontacji z językiem polskim . - Czpiga, Zofia (Przegląd Rusycystyczny, 2010)
РУССКИЕ МОДЕЛИ ПРЕДЛОЖЕНИЙ СО ЗНАЧЕНИЕМ ЖАЛОСТИ В СОПОСТАВЛЕНИИ С ПОЛЬСКИМ ЯЗЫКОМ Резюме В статье описываются русские предложения наречно-предикативной модели со значением жалости, сострадания с дательным субъекта в сопоставлении с польским языком. Изосемическая модель с предикативами жалко, жаль, обидно, неприятнo (N (Pron)d cop Adv) подвергается ряду структурно-семантических модификаций: 1. N (Pron)d cop Adv Na/g; 2. (cop) Adv; 3. N (Pron)d cop Adv Inf; 4. N (Pron)a cop Adv; 5. Nn Adv Vf; 6. Adv, что... В большинстве сучаев в польском языке эти структуры сохраня-ются, хотя появляются и другие модели с иной формой выражения субъекта, однако их семантика в основном сохраняется. Русские предикативы со значением жалости имеют в польском языке, кроме соварных, также различные текстовые эквиваленты, типа: другое наречие (обычно синонимическое), прилагательное, существительное, личная форма глагола. MODELS OF RUSSIAN SENTENCES WITH THE MEANING OF MERCY — IN COMPARISON WITH THEIR POLISH COUNTERPARTS Summary The article discusses Russian sentences of the adverbial-predicative type with the meaning of mercy, with Dative of the subject, in comparison with Polish language. The main model with predicates жалко, жаль, обидно, неприятнo (N (Pron)d cop Adv) undergoes certain structural and semantic alterations: 1. N (Pron)d cop Adv Na/g; 2. (cop) Adv; 3. N (Pron)d cop Adv Inf; 4. N (Pron)a cop Adv; 5. Nn Adv Vf; 6. Adv, что... In most cases Polish material preserves this type of structures, but other models can appear as well. In such cases usually it is the type of subject that differs, not its semantic features. Russian predicates with the meaning of mercy have in Polish language, apart from lexical, also textual equivalents, e.g. another adverb (usually a synonym), adjective, noun or verb.